2003
DOI: 10.1359/jbmr.2003.18.8.1506
|View full text |Cite
|
Sign up to set email alerts
|

Dentin Matrix Protein 1 Is Expressed in Human Lung Cancer

Abstract: We have previously shown that breast and prostate cancers express bone matrix proteins. DMP1 expression was evaluated in 59 human lung cancer samples at the protein and mRNA levels. It was detectable in 80% of the cases, suggesting a potential role for DMP1 in tumor progression and bone metastasis.Introduction: Previously, we and others have shown that bone extracellular matrix proteins such as bone sialoprotein (BSP) and osteopontin (OPN) are expressed in various types of cancer that are characterized by a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 16 publications
1
27
0
1
Order By: Relevance
“…Previous and relatively recent reports show the up-regulation of some SIBLINGs in different tumors, including oral cancers (Bellahcéne et al 1996;Waltregny et al 1998;Chaplet et al 2003;. At the same time, reports have indicated that the up-regulation of MMP-2, MMP-3, and/or MMP-9 is associated with increased aggressiveness of tumors (Birkedal-Hansen et al 1993;Brabletz et al 1999;Thomas et al 1999;Ogbureke et al , 2012.…”
Section: Discussionmentioning
confidence: 93%
“…Previous and relatively recent reports show the up-regulation of some SIBLINGs in different tumors, including oral cancers (Bellahcéne et al 1996;Waltregny et al 1998;Chaplet et al 2003;. At the same time, reports have indicated that the up-regulation of MMP-2, MMP-3, and/or MMP-9 is associated with increased aggressiveness of tumors (Birkedal-Hansen et al 1993;Brabletz et al 1999;Thomas et al 1999;Ogbureke et al , 2012.…”
Section: Discussionmentioning
confidence: 93%
“…BSP expression was been reported in breast (4,5), prostate (6), lung (7), and thyroid cancer (8). DMP1 has been shown to be strongly up-regulated in lung cancer (9). Elevated levels of MEPE mRNA expression by tumors from patients with hypophosphatemia and osteomalacia have been reported (10).…”
Section: Introductionmentioning
confidence: 99%
“…DMP1 was detected at high levels by Northern analysis in fetal bovine brain and cultured long bone as well as in odontoblasts (6). Most recently, DMP1 was localized by immunohistochemistry in human lung cancer tissue (7).…”
mentioning
confidence: 99%